The Effect of Tax Planning, Deferred Tax Assets, Deferred Tax Expenses and Tax Avoidance on Earning Management - Nuriah Isthifaiyyah; Pandowo, Hedi Pandowo; Kusumaningrum, Dian (Indonesian Scientific Publication, 2024)
The earnings management phenomenon that occurs in food and beverage sector manufacturing companies in Indonesia can influence the decisions of investors and other stakeholders in investing in shares. This research aims to determine the effect of tax planning, deferred tax assets, deferred tax expenses, and tax avoidance on earnings management in food and beverage sub sector companies listed on the Indonesia Stock Exchange for the 2018-2022 period. Agency theory is used as a foundation to explain the conflict of interest between principals and agents in company management. This research method uses a quantitative method with a causal associative approach. Secondary data collection techniques were collected through library research and financial report documentation from the website www.idx.co.id. The sample consists of 14 companies selected using purposive sampling techniques in the 2018-2022 period. Data analysis used the t-test (partial) with the SPSS version 25 statistical data processing tool. The research results showed that deferred tax expenses and tax avoidance had a significant effect on income management, while tax planning and deferred tax assets had no effect. Tax planning, deferred tax assets, deferred tax expenses and tax avoidance have a 94.4% effect on income management. In conclusion, companies tend to utilize deferred tax expenses and tax avoidance practices in earnings management. Further research is recommended to expand the scope of research and other variables that have the potential to influence earnings management.